2015
DOI: 10.1590/1982-021620156714
|View full text |Cite
|
Sign up to set email alerts
|

Uso de substâncias psicoativas, alterações vocais e qualidade de vida em usuários de drogas lícitas e ilícitas

Abstract: OBJETIVOS:investigar a qualidade de vida e voz, além das principais alterações perceptivo-auditivas e as medidas acústicas jitter, shimmer e Glottal Noise Excitation em usuários de substâncias psicoativas lícitas e/ou ilícitas que buscaram um centro de tratamento para dependência química.MÉTODOS:estudo transversal. Os participantes responderam aos questionários de Mensuração de Qualidade de Vida em Voze World Health Organization Quality of Life Instrument-Bref. Além disso foi realizado, um registro vocal da vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…We also observed another association of the presence of voice complaints in the population using alcoholic beverages and we verified this in other studies (18)(19)(20) . Frequent alcohol consumption was associated with laryngeal pathologies (19) and a study with an elderly population found that alcohol concomitant with smoking increased the risk of laryngeal diseases (20) .…”
Section: Discussionsupporting
confidence: 90%
“…We also observed another association of the presence of voice complaints in the population using alcoholic beverages and we verified this in other studies (18)(19)(20) . Frequent alcohol consumption was associated with laryngeal pathologies (19) and a study with an elderly population found that alcohol concomitant with smoking increased the risk of laryngeal diseases (20) .…”
Section: Discussionsupporting
confidence: 90%
“…In the context of this study, a short list of psychiatric medication that may have such side effects was excluded, including first-generation antipsychotics (chlorpromazine, haloperidol, loxapine, thioridazine), two or more second-generation antipsychotics (amisulpride, aripiprazole, clozapine, iloperidone, lurasidone, olanzapine, paliperidone, quetiapine, risperidone, ziprasidone, or use of high-dose benzodiazepines (diazepine>=30 mg/day, clonazepam>=2 mg/day, lorazepam>=4 mg/day, alprazolam>=2 mg/day). Additional exclusion criteria were substance abuse, defined as any of the following behaviors in the prior 12 months: 5+ alcoholic drinks in a single day, use of prescription drugs for non-medical use, use of illicit drugs, to avoid potential confounding effects on vocal production ( 57 , 58 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the context of this study, a short list of psychiatric medication that may have such side effects was excluded, including first-generation antipsychotics (chlorpromazine, haloperidol, loxapine, thioridazine), two or more second-generation antipsychotics (amisulpride, aripiprazole, clozapine, iloperidone, lurasidone, olanzapine, paliperidone, quetiapine, risperidone, ziprasidone, or use of high-dose benzodiazepines (diazepine>=30 mg/day, clonazepam>=2 mg/day, lorazepam>=4 mg/day, alprazolam>=2 mg/day). Additional exclusion criteria were substance abuse, defined as any of the following behaviors in the prior 12 months: 5+ alcoholic drinks in a single day, use of prescription drugs for non-medical use, use of illicit drugs, to avoid potential confounding effects on vocal production (60,61).…”
Section: Eligibility Criteriamentioning
confidence: 99%